Etnografi Upacara Adat Pernikahan Suku Jawa: Negosiasi Kebudayaan di Mukomuko Provinsi Bengkulu Dengan Integrasi Sosial dan Ekonomi - Ajeng Maya; Dhanurseto adiprashada; Mas Agus Firmansyah; Khavid Normasyhuri (Dinasti Review Publisher, 2024)
Adaptation in cross-ethnic traditional marriages often poses certain challenges, especially related to understanding and acceptance from both sides of the family. This research aims to find out how negotiations and cultural expressions occur between Javanese and other tribes in Penarik District, Mukomuko in carrying out traditional marriages. This research uses qualitative field research, specifically using analytical descriptive techniques. The research was conducted in Penarik District, Mukomuko Regency, Bengkulu Province. The data sources used include primary data and secondary data. The data used, namely secondary and primary, is used for. Primary data as the main data source consists of key and principal informants. The data collection approach includes several steps, namely literature study, interviews and documentation. The researcher explains how the credibility, dependability, transferability, and verifiability of data determines its validity and uses triangulation. The research findings show that the events of Javanese traditional marriages with other tribes in Penarik District, Mukomuko Regency, reveal how tolerance and cross-cultural understanding play a crucial role in overcoming differences that arise from multicultural interactions. During the assimilation of marriage negotiations, the Javanese and native Penarik people in Mukomuko used Indonesian, Mukomuko and Javanese as their daily languages; interact politely and courteously, especially when talking to those who are older or in a higher position; adapting religion, beliefs and norms that apply in society, without abandoning the culture of each extended family. The process of cultural adaptation and integration that occurs in the context of inter-ethnic marriage offers important insights into social dynamics and intercultural communication, as well as its practical implications in maintaining harmonious relationships in heterogeneous societies.